Would Population Aging Change the Output Effects of Fiscal Policy? - Honda, Jiro.; Miyamoto, Hiroaki (Washington, D.C. : International Monetary Fund, 2020)
Would population aging affect the effectiveness of fiscal stimulus? Despite the renewed focus on population aging, there are few empirical studies on the output effects of fiscal policy in aging economies. Our study fills this gap by analyzing this issue in OECD countries. We find that, as population ages, the output effects of fiscal spending shocks are weakened. We also find that, while high-debt countries generally face weaker fiscal multipliers, high-debt aging economies face even weaker multipliers. These results point to important policy implications: population aging would call for a larger fiscal stimulus to support aggregate demand during recession and thus require larger fiscal space to allow a wider swing of the fiscal position without creating concerns for fiscal sustainability. Our analysis also suggests that policy measures to promote labor supply could help increase the output effect of fiscal stimulus in aging economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet